Pengaruh Implementasi Platform Merdeka Mengajar dan Disiplin Kerja Guru Terhadap Hasil Belajar Siswa MTS Dayah Misbahul Ulum Paloh Kota Lhokseumawe - Musrizal, Musrizal; Mindawati, Mindawati; Yusuf, M.; Purnamasari, Purnamasari; Dodi, Iskandar (peusangan, 2024)
This research aims to analyze the effect of implementing the teaching independence platform and teacher work discipline on student learning outcomes. The research object took a sample of 35 MTS Misbahul Ulum Paloh teachers, Lhokseumawe city as a driving school that had implemented an independent curriculum. Using quantitative research with an infrential statistical approach, namely multiple regression analysis. The research results show several findings, namely: a). There is a convincing influence from the implementation of the independent teaching platform and teacher work discipline, both partially and simultaneously, on student learning outcomes. The influence of teacher work discipline is greater and simultaneously the contribution of these two factors is quite high, namely 64.8% of changes in student learning outcomes